A flower-inspired divergent light-trapping structure with quasi-spherical symmetry towards a high-performance flexible photodetector. Issue 40 (14th October 2020) - Liu, Sixiang; Tian, Junlong; Wu, Shu; Jia, Xilin; Luo, Minyuan; Zhang, Wang
Abstract : Molybdenum disulfide (MoS2 ) has received widespread attention in recent years due to its exciting properties. Abstract : Molybdenum disulfide (MoS2 ) has received widespread attention in recent years due to its exciting properties. However, the practical applications of MoS2 in optoelectronic devices are impeded by the power supply problem, the lack of flexibility, and the low light absorption for planar nanosheets and nanosheet arrays. Inspired by the elaborate architecture of the flower Tagetes erecta L., in this work, a self-assembled divergent MoS2 nanoflower (MoS2 _F) with quasi-spherical symmetry is successfully synthesized by a facile one-step hydrothermal method. It is of significance that coupled with asymmetric silver electrodes and packaged by polymethyl methacrylate (PMMA), a self-powered flexible photodetector (PD) based on MoS2 _F is actualized and shows an excellent flexible photoresponse performance at zero bias voltage. The divergent structure with quasi-spherical symmetry enables the MoS2 _F to achieve strong broadband and omnidirectional absorption (92.7%) and ensures that the MoS2 _F maintains the same physical contact on a different bending degree. Intriguingly, excellent flexibility and stability have been achieved as MoS2 _F PD retains 91.4% of the initial efficiency even when bent to 151° and retains 92.5% of the initial efficiency even after 1000 bending cycles. Therefore, by a low-cost process, this work demonstrates an innovative avenue to fabricate a self-powered flexible photodetector with excellent light absorption, broadband response, flexibility, and stability, which is of great practical significance for optoelectronic applications in various environments.